Belleville, Barbados. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This image shows a residential street, lined with houses and palm trees on both sides. This is a divided back postcard. Back of the postcard 00 INT 7 £3.50 (Handwritten in pencil). Published by Bruce Weatherhead, Barbados Pharmacy. Printed in Saxony
Landscape; Black & white; 3 ½” x 5½ ”
Keywords: Architecture; Roofs; Windows; Houses; Streets; Palms; Residential streets; Buildings; Architectural elements; Residences